TYPLEX® Chelate, a novel feed additive, inhibits Campylobacter jejuni biofilm formation and cecal colonization in broiler chickens - Khattak, Farina; Paschalis, Vasileios; Green, Matthew; Houdijk, Jos; Soultanas, Panos; Mahdavi, Jafar (Oxford University Press, 2018)
Reducing Campylobacter spp. carriage in poultry is challenging, but essential to control this major cause of human bacterial gastroenteritis worldwide. Although much is known about the mechanisms and route of Campylobacter spp. colonization in poultry the literature is scarce on antibiotic-free solutions to combat Campylobacter spp. colonization in poultry. In vitro and in vivo studies were conducted to investigate the role of TYPLEX® Chelate, a novel feed additive, in inhibiting Campylobacter jejuni (C. jejuni) biofilm formation and reducing C. jejuni and Escherichia coli (E. coli) colonization in broiler chickens at market age. In an in vitro study, the inhibitory effect on C. jejuni biofilm formation using a plastic bead assay was investigated. The results demonstrated that TYPLEX® Chelate significantly reduces biofilm formation. For in vivo study, 800 broilers (one-day old) were randomly allocated to 4 dietary treatments in a randomised block design, each having 10 replicate pens with 20 birds per pen. At day 21, all birds were challenged with C. jejuni via seeded litter. At day 42, caecal samples were collected and tested for volatile fatty acid (VFA) concentrations, C. jejuni and E. coli counts. The results showed that TYPLEX® Chelate reduced the carriage of C. jejuni and E. coli in poultry by 2 and 1 log₁₀ per gram caecal sample, respectively, and increased caecal VFA concentrations. These findings support TYPLEX® Chelate as a novel non-antibiotic feed additive that may help produce poultry with a lower public health risk of Campylobacteriosis.